Dynamics of Parliamentary Systems: Selections, Governments, and Parliaments - David P. Baron; Daniel Diermeier (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 1988)
This paper presents a theory of parliamentary systems that incorporates electoral, government formation, and legislative institutions and focuses on the strategic opportunities inherent in those institutions. The electoral system is proportional representation, and a party is selected as formateur based on its representation in parliament. Parties are assumed to be unable to commit credibly to the policies they will implement once in government. Since the policy chosen by a government in one period becomes the status quo for the next period, a current govemment can strategically position the status quo to affect both the outcome of the next election and subsequenty government formation. When parties have both policy and officeholding preferences, elections are not moderating; i.e., they do not contribute to policy centrality or stability. Policies can be outside the Pareto set, and governments as well as policies change with each election. Those governments are formed by minimal winning coalitions.
Keywords: 330